Effect of water migration rate on the deformation characteristics of wheat starch/gluten extruded noodles. (15th June 2022) - Gong, Yanfei; Meng, Ang; Zhang, Yingquan; Zhang, Bo; Ying, Danyang; Guo, Boli; Wei, Yimin
Abstract: Excessive deformation destroys the structure of wheat flour-based noodles. Wheat starch/gluten extruded noodles with various starch contents were made by an extruder and dried under various relative humidities to control noodle deformation. The difference between water activity (aw) and relative humidity (RH) includes three models: decrease model [(aw-RH) 33%→6%], constant model [(aw-RH) 22%→23%], and increase model [(aw-RH) 22%→40%]. The water migration rate was high when the difference increased, or the starch content was relatively high. When the extruded noodles are in the glass state, the relatively high water loss rate, induced by the model of [(aw-RH) 22%→40%], causes a high change ratio of slice area, rough area ratio, and concavity percentage of extruded noodles. Therefore, the water loss rate and deformation degree of wheat starch/gluten extruded noodles can be controlled by the difference between the water activity of noodles and the relative humidity of the environment. Highlights: Decrease, constant, and increase (water active-relative humidity) models were set. The starch/gluten extrudate deformation ratio was analyzed by image analysis. The water loss rate was high when (water active-relative humidity) was high. Extrudates deform severely when (water active-relative humidity) was large. (Water active-relative humidity) control water loss rate and extrudate deformation.